Are Sportive Games Affecting the Lipid Profile in Adolescents? - Vedat Çınar; Taner Akbulut; Yakup Kılıç; Zarife Pancar (Selcuk University, 2019)
The purpose of this study was to investigate the effects of sportive games on the lipid profile in some selected branches for ten weeks applied to adolescents. 11-14 age range; A total of 52 children, 26 in the study group and 26 in the control group, participated voluntarily in research. While the participants in the control group were only attending physical education lessons, participants in the research group played sport games for ten weeks, three times in a week, 60 minutes in a day different branches. Blood samples were taken from both groups two times before and after ten weeks of the program. Cholesterol, Triglyceride, HDL, LDL and VLDL cholesterol levels of were determined in taken blood samples. The obtained data were analyzed in the SPSS 22.0 Package program. Independent samples t test was used to determine differences between groups, and Paired samples t test was used to determine intra-group differences. When the pretest values ​​of the participants were compared, there was no difference between the groups in the values ​​of Cholesterol, Triglyceride, HDL, LDL and VLDL Cholesterol  (p gt;0,05), HDL cholesterol levels were different in favor of the study group when the post test values ​​were compared. In the intra-group evaluations, there was no difference between the pre-post tests values ​​of the control group, it was determined that the research group had differences in the levels ​​of cholesterol and HDL cholesterol (p lt;0,05). As a result, sportive games that applied throughout ten weeks to adolescents had positive effects on lipid profile, it can be said that they may have a health promoting role if they are made permanent.